Supporting the “Casa Lar” social educator: a case study of a consultation using intercultural knowledge translation/Apoiando o educador social no Casa Lar: um estudo de caso de uma consulta usando translação de conhecimento intercultural - Strong, Debra Marie (Cadernos Brasileiros de Terapia Ocupacional, 2018)
Children living in foster care have the right to live in a supportive and caring environment, yet studies show that many foster caregivers find it challenging to adequately meet the child’s individual needs. Organizations providing services to children in foster care are responsible for supporting caregivers in this role. This case study describes an occupational therapy (post-professional master’s student) consultation with a group foster home (Casa Lar), in São Paulo, Brazil, to implement a training and support program for their caregivers. A needs assessment revealed the necessity to implement a comprehensive professional development program, based on organizational values and caregiving competencies. Using the Canadian Practice Process Framework as a guide, a multicultural group of clinician administrators completed a cycle of knowledge translation to identify current knowledge in the area, and adapt it to the local context. Active learning and participant action strategies were included in the training program, with a plan to jointly develop a knowledge translation tool that will enable a change in caregiver practice. We present plans for a formative and summative program evaluation, along with reflections on the enabling nature of the consultation.